2014
DOI: 10.1007/s11069-014-1522-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of SMF tsunami hazard along the upper US East Coast: detailed impact around Ocean City, MD

Abstract: With support from the US National Tsunami Hazard Mitigation Program (NTHMP), the authors have been developing tsunami inundation maps for the upper US East Coast (USEC), using high-resolution numerical modeling. These maps are envelopes of maximum elevations, velocity, or momentum flux, caused by the probable maximum tsunamis identified in the Atlantic oceanic basin, including from far-field coseismic or volcanic sources, and near-field Submarine mass failures (SMFs); the latter are the object of this work. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 34 publications
1
77
0
2
Order By: Relevance
“…However, dispersion is also key to model the coastal impact of any tsunami since dispersive shock waves (a.k.a. undular bores) can be generated near the crest of long waves in increasingly shallow water (MADSEN et al 2008;GEIST et al 2009;GRILLI et al 2012GRILLI et al , 2015b. A review of dispersive effects in tsunamis can be found in GLIMSDAL et al (2013).…”
Section: Modeling Of Near-and Far-field Tsunami Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…However, dispersion is also key to model the coastal impact of any tsunami since dispersive shock waves (a.k.a. undular bores) can be generated near the crest of long waves in increasingly shallow water (MADSEN et al 2008;GEIST et al 2009;GRILLI et al 2012GRILLI et al , 2015b. A review of dispersive effects in tsunamis can be found in GLIMSDAL et al (2013).…”
Section: Modeling Of Near-and Far-field Tsunami Impactmentioning
confidence: 99%
“…Additionally, wave breaking dissipation is adequately modeled by switching from the Boussinesq to the NSWE equations when the local height to depth ratio exceeds 0.8 (which has been shown to closely approximate the physical dissipation in breaking waves). Bottom friction is parameterized as a quadratic term based on a friction coefficient C d ; in all the present simulations, we use the standard value for coarse sand, C d ¼ 0:0025, which only causes moderate dissipation, except for long distances of propagation over wide shallow shelves; hence this value is conservative as far as predicting maximum flow depth at the coastline; see GEIST et al (2009) andGRILLI et al (2015b) for a study of the influence of bottom friction on landslide tsunami nearshore propagation and coastal impact. Additional discussions in this respect can be found in KAISER et al (2011).…”
Section: Modeling Of Near-and Far-field Tsunami Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…However, individual damage depends on local building structure and design, even under the same hydrodynamic conditions. Moreover, wavestructure interaction is difficult to model [Petukhin et al, 2012], and many models remove buildings to allow for more efficient calculations [see Westerink et al, 2008;Parsons et al, 2014;Yao et al, 2014;Grilli et al, 2015]. Such simplifications can result in errors in hydrodynamic outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Asumiendo una tradición importante que defi ne el riesgo natural como la plasmación territorial de una actuación humana poco acorde con las características físico-naturales del territorio donde tiene lugar (Blaikie et al, 1994;Rojas y Martínez, 2011), los factores principales están dados por la valoración de las condiciones asociadas a la amenaza (tsunami) y a la vulnerabilidad, que defi nen el riesgo. En el caso de la amenaza, la atención ha estado en determinar a través de modelamiento numérico, el comportamiento hidrodinámico del tsunami y su impacto en la infraestructura, especialmente a través de curvas de fragilidad (Suppasri et al, 2011;Mas et al, 2012;Sugawara & Goto, 2012;Grilli et al, 2015;Prerna et al, 2015). Por su parte, la vulnerabilidad ha sido uno de los aspectos más discutidos por su difícil valoración en los procesos sociales y territoriales cambiantes.…”
unclassified